2018
DOI: 10.1111/pace.13581
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac resynchronization therapy improves myocardial conduction

Abstract: Background Cardiac resynchronization therapy (CRT) reverses left ventricular remodeling and improves left ventricular systolic function. However, little is known about whether CRT improves ventricular conduction. Objective To determine the relationship between CRT response and QRS narrowing. Methods The study included consecutive patients who underwent CRT with defibrillator (CRT‐D) implantation between January 2002 and December 2012 and had subsequent generator replacement (GR). At the time of GR, super‐respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Reverse electrical remodeling can be also detectable in shortening of paced QRS duration during chronic CRT. Yang et al assessed changes of paced QRS during longtime follow-up and found that narrowing of paced QRS was significant in responders after 6 month of biventricular pacing and super-responders (defined as LVEF ≥ 50%) had a further reduction of paced QRS duration measured at time of generator replacement [41].…”
Section: Paced Qrs Durationmentioning
confidence: 99%
“…Reverse electrical remodeling can be also detectable in shortening of paced QRS duration during chronic CRT. Yang et al assessed changes of paced QRS during longtime follow-up and found that narrowing of paced QRS was significant in responders after 6 month of biventricular pacing and super-responders (defined as LVEF ≥ 50%) had a further reduction of paced QRS duration measured at time of generator replacement [41].…”
Section: Paced Qrs Durationmentioning
confidence: 99%